THE IMPORTANCE OF DRIVERS' AGE AND EXPERIENCE IN ENSURING ROAD SAFETY - N. Sh. Gulyamov; B. A. Aliboyev; N. R. Aslonov; J. A. Axunov (Modern American Journals, 2025)
This article analyzes road traffic accidents recorded across the Republic of Uzbekistan during 2023–2024, with a particular focus on the relationship between drivers’ age and driving experience and their impact on road safety. The study provides data-driven insights into the correlation between age groups and the types of traffic rule violations that commonly lead to accidents. Additionally, international best practices are examined, and practical recommendations are proposed to reduce accidents involving inexperienced or high-risk drivers. The article emphasizes the need for progressive training, enhanced responsibility awareness, and tailored preventive strategies based on age-specific risk profiles.
Keywords: driver, road traffic accidents, age experience, skill, inexperience, risk tendency, sense of responsibility, step-by-step